Ellipticity ratio effects in the energy absorption of axially crushed composite tubes - Alkoles, O.M.S.; Mahdi, E.; Hamouda, A.M.S.; Sahari, B.B. (Springer, 2003)
In this paper, the influence of ellipticity ratio on energy absorption capability and load-carrying capacity of woven roving wrapped composite elliptical tubes has been investigated both experimentally and numerically. A series of experiments was conducted for composite elliptical tubes with ellipticity ratios (a/b) ranging from 1 to 2. Typical failure histories of their failure mechanism are presented and discussed. The experimental data are correlated with predictions from a finite element model. Load-deformation curves and deformation histories of typical specimens are presented and discussed. For all specimens considered, classical axial collapse eigenvalues were computed. The results showed that the ellipticity ratio significantly influenced the energy absorption capabilities as well as the load-carrying capacity. Tubes with ellipticity ratios of a/b 1.25 and 2.0 displayed the highest normalised specific energy absorption capability. A reasonable agreement between the experimental and computational results was obtained for the critical crush load.